The effect of conscious mindfulness-based informative approaches on managing symptoms in hemodialysis patients - Akbulut, Gönül; Erci, Behice (Frontiers in Psychology, 2024)
The research was conducted to determine the effect of conscious mindfulness based informative approaches applied in hemodialysis patients on reducing stress and managing symptoms. This research was conducted as a real experimental model with a control group. Research population consisted of 160 hemodialysis patients. The sample of the study was determined as 120 hemodialysis patients in total, 60 in the experimental and 60 in the control group, as a result of the power analysis. After the pre-test application, a mindfulness-based stress reduction program was applied to the experimental group. In the analysis of the data collected in the research, percentage, frequency, chi-square analysis, t test for independent groups, t test for dependent groups were used by means of SPSS for Windows 22.00 statistical software package the t test analyses of the differences between pre-test and post-test scores of hemodialysis patients in the experimental group were found to be significant in favor of the post-tests. It was found out that the conscious mindfulness-based informative approaches decreased the perceived stress and anxiety of the patients in the experimental group, whereas increased their levels of conscious mindfulness and symptom management.